2019
DOI: 10.1186/s12879-019-4481-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional intakes and associated factors among tuberculosis patients: a cross-sectional study in China

Abstract: BackgroundThe objectives of this study were to examine nutrient intakes of tuberculosis (TB) patients and to identify their associated factors.MethodsIn this cross-sectional study, 300 adult TB patients were surveyed in two impoverished counties in China. Nutrient intakes were evaluated through two consecutive 24-h dietary recalls and compared with the Chinese Dietary Reference Intakes (DRIs) 2013. The potential socio-demographic and behavioral factors were analyzed using multivariate logistic model to identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
4
25
1
1
Order By: Relevance
“…Many previous studies reported that nutritional status is an important factor in TB treatment (25,26). Malnutrition leads to a decrease in immunity and M. TB is susceptible to infection; on the other hand, increased consumption of TB leads to malnutrition in the body.…”
Section: Mortality Risk Factors Of Tb Patients With Respiratory Failure During Icu Treatmentmentioning
confidence: 99%
“…Many previous studies reported that nutritional status is an important factor in TB treatment (25,26). Malnutrition leads to a decrease in immunity and M. TB is susceptible to infection; on the other hand, increased consumption of TB leads to malnutrition in the body.…”
Section: Mortality Risk Factors Of Tb Patients With Respiratory Failure During Icu Treatmentmentioning
confidence: 99%
“…Through univariate analysis, we determined the variables (BMI, marital status) related to treatment outcome. Additionally, variables previously reported to be associated with outcome (age (33) , sex (33) , education completed (34) , occupation (35) , smoking (36) , drinking (36) , regular exercise (37) and total energy intake (38) ) were considered potential confounders. The crude model was unadjusted; model 1 was adjusted for age and sex; model 2 was adjusted for age, sex, BMI, education completed, occupation, marital status, smoking, drinking, regular exercise and total energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…A cross sectional study in China by Ren et al showed that TB patients have insufficient daily energy-protein intake compared with the Chinese Dietary Reference Intakes (DRIs) 2013. Also they are insufficient of many micronutrients daily intake [19]. Macronutrients including carbohydrate and fat are converted to energy, while protein and some fat are used to make structural and functional components of human tissue.…”
Section: Introductionmentioning
confidence: 99%